2011
DOI: 10.4269/ajtmh.2011.10-0545
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cross-Reactivity of Various 56 kDa Recombinant Protein Antigens with Serum Samples Collected after Orientia tsutsugamushi Infection by ELISA

Abstract: Orientia tsutsugamushi, the etiologic agent of scrub typhus, has a highly expressed and immunodominant 56-kD outer membrane protein. This protein is one of the leading candidates for diagnosis and vaccine development for scrub typhus. Previous studies using recombinant 56-kD protein (r56s) derived from Karp strain (Kpr56) in a mouse model have shown good homologous protection but only moderate to poor heterologous protection. We evaluated the cross-reactivity of recombinant 56-kD proteins from Karp, Kato, Gill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…The sequence of the variable domain 1 was replaced by that in TA763 with modifications as described. 11 The DNA was synthesized by Bioclone (San Diego, CA) and cloned into a pET29a vector (Novagen, Madison, WI) with built-in Nde I and Xho I restriction sites. The synthesized DNA sequences were confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…The sequence of the variable domain 1 was replaced by that in TA763 with modifications as described. 11 The DNA was synthesized by Bioclone (San Diego, CA) and cloned into a pET29a vector (Novagen, Madison, WI) with built-in Nde I and Xho I restriction sites. The synthesized DNA sequences were confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…31 The serodiagnosis of scrub typhus depends on the less sensitive Weil-Felix test and immunofluorescence test, which are expensive and require expertise. 33,34 There is some evidence that the 47-kDa protein of O. tsutsugamushi may have the potential to initiate autoimmune response because of the cross-reaction with human HtrA protein due to the presence of homologous amino acid sequences. 32 The 56-kDa antigen was reported to show high antigenic variation and the antibodies are not cross-reactive.…”
Section: Discussionmentioning
confidence: 99%
“…These protein aggregates were once considered to be waste products, but recent discoveries have revealed that inclusion bodies actually contain biologically active polypeptides [13]. The inclusion bodies purified in this study were denatured using the Bug Buster protein extraction kit, and sequential reduction in urea concentration was used to refold the denatured protein [14]. …”
Section: Discussionmentioning
confidence: 99%